Assessment of foodborne illness awareness and preferred information sources among students in Saudi Arabia: A cross-sectional study. (June 2020) - AL-Mohaithef, Mohammed; Padhi, Bijaya K.; Shameel, Mohammed; Elkhalifa, Ahmed M.E.; Tahash, Mohammed; Chandramohan, Sriram; Hazazi, Ahmed
Abstract: Background: Foodborne diseases (FBD) is becoming a significant public health concern in both developed and developing countries. Young adults are the most vulnerable demographic of food poisoning. While research has indicated that young adults are undereducated in food poisoning knowledge, studies examining the knowledge of young Arabian, as well as approaches to improve their education, have not been conducted. The study objective was to assess foodborne illness and preferred information sources among students in the Kingdom of Saudi Arabia (KSA). Methods: We designed a cross-sectional study among Saudi Electronic University students (N = 429) located across major geographic locations in KSA. A questionnaire pertaining to knowledge on food poisoning was administered to registered students. A score of 1 was given to the right answer, and 0 to the wrong answer. A multiple logistic regression model was developed to predict the relationship between the dependent variable (overall knowledge score) and the independent variables (demographic, the field of study, education level, and geography). Results: Respondents were, on average, 24.2 ± 4.5 years old. The majority of the students belongs to Riyadh (30.2%), Abha (27.5%), Dammam (22.6%), and Jeddah (15.9%) campus. About half of the students were female. Most of the students (78.6%) were from the bachelor level of education. Students field of study varies across domains; the majority of them belongs to the health sciences field. Of the 429 respondents, 85.5% of students know the causes of food poisoning. However, half of them don't know the difference between food infection and food intoxication. 27.3% of students don't recognize the source of food that is more likely associated with foodborne disease. Multivariate analyses indicates that the field of study category was associated with the poor knowledge of the causes of foodborne illnesses among the study participants. Compared with health sciences, students belonging to the computer science field were relatively low knowledge on the cause of food poisoning (Odds Ratio: 3.37; 95% CI: 1.15–7.51), and they are also less likely to differentiate between food infection and food intoxication (Odds Ratio: 3.95; 95% CI: 1.81–8.60). 42.9% of students visit a doctor to seek information about food poisoning, and 39.9% visit government website followed by social media (39.6%) for information on food poisoning. Conclusion: Students in this survey were fairly knowledgeable about foodborne diseases, and most of them used an authentic source of information for their knowledge. Our study is consistent with other similar studies, and educational institutions can play an essential role in food safety education while targeting health education and promotion. These results warrant the need for a health education program in creating greater awareness of foodborne diseases among students. Highlights: Foodborne disease knowledge in young Arabian adults is low. Common causes of foodborne illness are overlooked or not often recognized. There is a need for stronger, more targeted foodborne disease education programs. Students preferred to use authentic information sources for their knowledge. Educational institutions could play an important role in food safety education programs.